1996
DOI: 10.1111/j.1600-0447.1996.tb09815.x
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia. II. Treatment with lorazepam and electroconvulsive therapy

Abstract: Case material and retrospective studies support the use of both lorazepam and ECT in treating catatonia, but few prospective investigations exist and none employ quantitative monitoring of response. In this study we test their efficacy in an open, prospective protocol, and define a "lorazepam test' with predictive value for treatment. Twenty-eight patients with catatonia were treated systematically with parenteral and/or oral lorazepam for up to 5 days, and with ECT if lorazepam failed. Outcome was monitored q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
195
1
24

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(241 citation statements)
references
References 51 publications
11
195
1
24
Order By: Relevance
“…This interesting observation is in line with a previous study reporting 32% of patients had resolution of psychotic symptoms once catatonia was effectively treated. 14 This effect may be explained by the collateral impact of treatments directed at catatonia on psychotic symptoms, or by a worsening in psychotic symptoms by catatonia, which improves secondarily as catatonia is treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interesting observation is in line with a previous study reporting 32% of patients had resolution of psychotic symptoms once catatonia was effectively treated. 14 This effect may be explained by the collateral impact of treatments directed at catatonia on psychotic symptoms, or by a worsening in psychotic symptoms by catatonia, which improves secondarily as catatonia is treated.…”
Section: Discussionmentioning
confidence: 99%
“…14 This is an important issue in treating patients presenting with both psychosis and catatonia. We found that clozapine stood out uniquely as an antipsychotic agent that was uniformly beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Catatonia evaluation scales have rarely been used in studies that measure response to treatment. Nevertheless, one study has already shown that the BFCRS is sensitive to the changes in the severity of the catatonic symptoms during treatment with lorazepam and electroconvulsive therapy 26 . Despite being considered valid and widely used, a lack of uniformity and the existence of inaccurate definitions and symptoms are said to be some of its limitations 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutically, 60-80% of the acute catatonic patients respond to lorazepam, a GABA-A receptor agonist. 4 We report a case of periodic catatonia that responded well to olanzapine.…”
mentioning
confidence: 99%